Variation in biomass and nutrients allocation of Corydalis hendersonii on the Tibetan Plateau with increasing rainfall continentality and altitude - Qien Li (Elsevier, 2021)
The Tibetan Plateau is considered as one of most sensitive region to global change. Nutrient (N and P) availability is an important limiting ecological factor in cold terrestrial ecosystems such as the alpine belt of the Tibetan Plateau. We focused on Corydallis hendersonii, an endemic alpine species of the Tibetan Plateau. Exploring the N and P below- and above-ground responses of C. hendersonii to climatic factors is crucial for biodiversity conservation of the alpine Tibetan plateau under global change. We used the Outlying Mean Index and regression analyses to assess N and P stoichiometry and biomass responses in leaves and roots of C. hendersonii along climatic gradients. We found that investment and allocation of nutrient and biomass in C. hendersonii were mainly driven by rainfall continentality. In the eastern less-continental wet area of the Tibetan plateau, C. hendersonii had higher biomass in leaf, and lower N and P investment in roots than in the western more continental dry part. Specifically, 300 mm year−1 Mean annual precipitation (MAP) and ca. 80° Rainfall continentality index (GAMS) were threshold values of climate stress inducing strong nutrient limitation for C. hendersonii across the Tibetan Plateau. Our results suggest that rainfall continentality is the primary climatic driver of variation in biomass and nutrients allocation of C. hendersonii on the Tibetan Plateau. Thus, global warming and drying should induce a decrease in total biomass, a reduction in leaf N and P concentrations and an increase in root/shoot ratio in the alpine region of the Tibetan Plateau.